PENGARUH PENGENBANGAN KARIER TERHADAP PRODUKTIVITAS PEGAWAI RUMAH SAKIT UMUM DAERAH KABUPATEN ROKAN HULU - -, Juwita (Jurnal Mahasiswa Prodi Manajemen Fakultas Ekonomi, 2016)
To determine the research goals of career development Employed General Hospital of Rokan Hulu. To know Employed Produktivity District Genetral Hospital of Rokan Hulu. For determine the effect on Produktivity of career development Employed General of Rokan Hulu. The population was Servants Regional General Hospital Rokan Hulu of 48 people with the techniques of randon saturation,where all individuals in the population either individually or random saturation, where all individuals in the populasion either individually or jointly given an equal opportunity to be elected as members of the sample Methods of Observation,mentods of questionnaires, documents,archives, influence the development of career development opportunities Employed Hospital Rokan Hulu indicator Validity, completeness, comparable, inclusive rapid and timely, to influence the effectiveness of Employed Produktivity General Hospital of Rokan Hulu . From the analysios result showed that the respondent influence on the productivity of an employee’s career development Rokan Hulu general Hospital .From the results of data processing can be conclude alpha 225n>0.60, working career development of Y Productiviy Hospital Rokan Hulu. Keywords : Career Development and Productivity